Pengaruh Desentralisasi Fiskal dan Korupsi Terhadap Pertumbuhan Ekonomi di Provinsi Bali - Yudistira, Ida Bagus; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
This research’s title is determine the effect of fiscal decentralization and corruption on economic growth in the province of Bali.It was found that simultaneous independent variables are fiscal decentralization and corruption significant effect on the dependent variable is economic growth in the province of Bali.It can be seen from the calculated F value greater than the F table that is equal to 14.318.Partially fiscal decentralization does not affect the economic growth in the province of Bali.Partially corruption does not affect the economic growth in the province of Bali.The purpose of this study was to determine the effect of fiscal decentralization and corruption on economic growth in the province of Bali.This research was conducted in the province of Bali.Data analysis techniques used in this research is multiple linear regression.
Keywords: Fiscal Decentralization; Corruption; Economic Growth